Seeing the world differently: variability in the photosensory mechanisms of two model fungi. (26th October 2015) - Dasgupta, Arko; Fuller, Kevin K.; Dunlap, Jay C.; Loros, Jennifer J.
Summary: Light plays an important role for most organisms on this planet, serving either as a source of energy or information for the adaptation of biological processes to specific times of day. The fungal kingdom is estimated to contain well over a million species, possibly 10‐fold more, and it is estimated that a majority of the fungi respond to light, eliciting changes in several physiological characteristics including pathogenesis, development and secondary metabolism. Two model organisms for photobiological studies have taken centre‐stage over the last few decades – N eurospora crassa and A spergillus nidulans . In this review, we will first discuss our understanding of the light response in N . crassa, about which the most is known, and will then juxtapose N . crassa with A . nidulans, which, as will be described below, provides an excellent template for understanding photosensory cross‐talk. Finally, we will end with a commentary on the variability of the light response among other relevant fungi, and how our molecular understanding in the aforementioned model organisms still provides a strong base for dissecting light responses in such species.